IMPLEMENTASI FINANCIAL MODELING FRAMEWORK (FMF) TERINTEGRASI: DEMONSTRASI INTEGRASI LAPORAN KEUANGAN DAN TRANSMISI RASIO KINERJA BERBASIS SPREADSHEET - Iman Sjamsu Rahardjo (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This study proposes and demonstrates the operational implementation of an integrated Financial Modeling Framework (FMF) as a response to the structural fragmentation commonly found in spreadsheet-based corporate financial models. Unlike conventional projection models that operate in partial or disconnected formats, FMF v1.8 adopts a modular architecture built upon an assumptions layer that systematically integrates the Income Statement, Balance Sheet, and Cash Flow Statement while transmitting driver changes into performance ratios. Using an artifact-based demonstrative approach, the study provides evidence that strategic assumption adjustments—such as revenue growth and capital structure changes—are consistently transmitted to financial statement structures and key ratios (ROE, ROA, DER) without generating balance sheet inconsistencies or cash flow distortions. The findings confirm the existence of a structured ratio transmission mechanism, positioning the model not merely as a forecasting tool but as an integrated analytical framework capable of mapping financial trade-offs transparently. Theoretically, this research extends the financial statement integration literature by providing implementation-level evidence of an integrated modeling architecture. Practically, FMF offers a more robust driver-based framework for sensitivity analysis, scenario evaluation, and structured financial decision making.